Subtractive renormalization of the next-to-leading order NN interaction - Timoteo, V. S.; Frederico, T.; Delfino, A.; Tomio, Lauro (Elsevier B.V., 2007)
The subtracted kernel method is implemented recursively to solve scattering equations for the S-1(0) phase-shifts considering the leading and the next-to-leading order NN interaction.